Effectiveness of melodic intonation therapy in the management of communication difficulty of pupils with non-fluent aphasia in the classroom setting (2012)
This study was conducted to evaluate the effects of melodic intonation therapy in the management of children with non-fluent aphasia. Twelve (12) samples of six (6) each in the two groups of experimental and the control were purposively selected from a Speech/Language Clinic in Ibadan, Oyo state, Nigeria. Melodic intonation therapy was the technique used with the samples in the experimental group, while those in the control group were rehabilitated through regular speech therapeutic exercises. With the aid of t-test statistics at 0.05 level of significance, the findings revealed a significant difference between the performances of the two groups. The outcome indicated that the experimental group performed significantly above those exposed to regular speech therapy (Cal. t=8. 06, Crit.t=1.18, df = 10, P<.05). The results of the study showed that training effects yielded more superior gains than the pre-evaluation results (Cal.t=10.95, crit.t=1.18, df=10, P<.05). The paper therefore, recommends the use of melodic intonation therapy with the non- fluent aphasia and any other patients with speech impairment. Also, the paper concludes with some guidelines and suggestions to be followed in using the therapeutic package for effective gains.